Characterisation of a Novel Series of Aprotinin-Derived Anticoagulants - Stassen, Jean Marie; Lambeir, Anne-Marie; Matthyssens, Gaston; Ripka, William C; Nyström, Åke; Sixma, Jan J; Vermylen, Jos (Thrombosis and Haemostasis, 1995)
Previous investigations have indicated that interference with the initial level of the blood coagulation may lead to effective antithrombotic therapy. Recently a series of potential coagulation inhibitors derived from bovine pancreatic trypsin inhibitor (BPTI, aprotinin) was described. We have determined their inhibition constants, effects on coagulation assays, effects in an in vitro human thrombosis model and pharmacological profiles in hamsters. The aprotinin-derived analogues (4C2,7L22, 5L15, 6L15, 5L84) showed significantly increased inhibitory activity towards factor Xa, factor Vlla-tissue factor (TF) complex, factor XIa and plasma kallikrein or a combination of them, and a significantly decreased plasmin inhibition as compared to aprotinin. In the coagulation assays, 4C2 and 7L22 mainly inhibited factor Xa, 5L15 and 6L15 inhibited factor VIIa-TF complex and 5L84 inhibited factor Xa, factor VIIa-TF complex and the contact activation. In flow chamber experiments with human blood 7L22, 5L15, 6L15, 5L84 and rTAP significantly inhibited fibrin formation and platelet deposition on extracellular matrix from phorbol ester stimulated human endothelial cells both under high and low shear stress and in the presence of low molecular weight heparin. The pharmacological profiles of the aprotinin analogues and rTAP with a mean residence time of 64 to 140 min were not significantly different. Modification of an aprotinin analogue with PEG (5L15-PEG) resulted in a 10-fold decrease of the inhibition constant for the factor VIIa-TF complex and in a significant prolongation of the secondary half-life, while the initial half-life was unchanged.Thus the investigated aprotinin-derived coagulation inhibitors resulted in a series of combined coagulation inhibitors with a pharmacological behaviour, which justifies in vivo testing of their potential antithrombotic action, as reported in the accompanying paper.